The Presence and Characteristics of Female Directors: How They Influence Firm Performance - Stevanus Pangestu; Silvia Gunawan; Jeremy Surya Wijaya (School of Business, IPB University (SB-IPB), 2019)
This research aims to assess the effects of female directors’ presence and characteristics on firm profitability, measured with Return on Assets. Observed characteristics include education, age, and foreign nationality. 364 publicly-traded non-financial Indonesian corporations were observed from 2013 to 2016 (n=1,456). Our fixed effects panel regression analysis finds that the presence of female directors on the board positively influences profitability: women bring in a productive dynamic that complements the style of the male-dominated board. Meanwhile, none of the other independent variables significantly affect ROA, signifying that our results do not correspond with Upper Echelons theory. We also recommend corporations to appoint female board members based on merits and not just for the sake of diversity, as they may improve firm performance.Keywords: female directors, firm performance, profitability, upper echelons, corporate governance